Etika lingkungan dan penyadaran ekologis dalam novel Gurattala karya Candrika Adhiyasa: Kajian ekokritik sastra - Hermawan, Aa; Halimah, Halimah (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
Literature serves as an important medium to reflect on the global ecological crisis. This study examines how Gurattala, a novel by Candrika Adhiyasa, critiques the impact of development by mapping the relationship between ecological destruction and social injustice. This research employs a descriptive qualitative design using a literature study method. The analysis was conducted through close reading of the primary data (the novel), framed by Greg Garrard’s conceptual approach to ecocriticism. The findings reveal that environmental degradation in Gurattala includes industrial pollution and deforestation, which are causally linked to the dispossession of living spaces and the marginalization of local communities. The novel argues that the ecological crisis is essentially a social crisis. As a resolution, Gurattala does not offer technical or political solutions but rather an ethical one, embodied in the protagonist’s contemplative journey toward an ecocentric awareness. This study concludes that Gurattala employs speculative fiction as a powerful medium for ecological critique, not merely to convey a moral message but to present a profound reflection on the interconnectedness of humans and nature in the modern era.